The Influence of Discipline, Motivation, and Compensation on Teachers' Self-Perception of Performance - Rahayu, Gita; Santoso, Joko Bagio; Akhmadi, Ali; Nafisah, Siti; Mustika, Maya (SAN Scientific, 2024)
This study aims to determine the effect of the variables of discipline, work motivation and compensation on the performance of state junior high school teachers in the Koja area of North Jakarta. The research was conducted at SMP Negeri 30, SMP Negeri 277 and SMP Negeri 151. The sampling technique in this study used a saturated sampling technique. Saturated sampling technique is a sampling technique when all members of the population are sampled and are relatively small. The results of the study show that the variable of discipline has an effect on teacher performance, motivation has an effect on teacher performance and compensation has had an effect on teacher performance. The results of hypothesis testing show that the variables of discipline, motivation and compensation together have a significant effect on teacher performance.